Midwifery Care For Maternity In Ny.S Age of 29 Years 39 Weeks Of Pregnancy G3 P2 A0 With Ambiances Early Rupture (Kpd) At Al-Fitrah Pratama Clinic Tanjung Temple - Tri Suci Dewi Wati; Miranti (Science Midwifery, 2021)
Premature rupture of membranes is still a health problem in Indonesia with a high incidence and mortality rate.According to WHO, the incidence of premature rupture of membranes (PROM) ranges from 5-10% of all births. Preterm PROM occurs in 1% of all pregnancies and 70% of cases of PROM occur in term pregnancies. In 30% of cases PROM is the cause of premature birth. The incidence of PROM in Indonesia ranges from 4.5-7.6% of all pregnancies. Able to increase knowledge, skills, and experiencewhich is evident in providing midwifery care to Mrs. SG3 P2 A0 at PMB Sri Kurniawati AM.Keb with premature rupture of membranes in 7 steps Varney. Descriptive observational is a case study approach. Descriptive research method is a research method carried out with the main aim of making an objective picture of a situation.After providing midwifery care to Mrs. S, the results of midwifery care were: general condition was good, consciousness: composting, Vital Signs BP: 110/80 mmHg, Pols: 80 x/i, RR: 24 x/i. Temp: 36️C. Bleeding: none, empty bladder, TFU: 1 finger below center. There was no maternal infection, delivery was normal, mother and child survived. There was no gap between theory and practice in the midwifery care provided to Mrs. S.